Effect of Methylmethacrylate and Ethylenediamine on the Physicomechanical Properties of High Strength Portland Cement: Effect of Additives on Portland Cement - Amin, Noor-ul- (Biological Sciences - PJSIR, 2009)
In the study of the effect of methylmethacrylate (C5H9O2) and ethylenediamine (C2N2H8) on the physicomechanical properties of high strength Portland cement, addition of methylmethacrylate upto 5% strength showed negative effect on the bulk density, cold crushing strength and hydration of the cement; however, the negative effect was relatively less in case of lower concentrations (< 2%). Addition of ethylenediamine upto 3% concentration showed remarkable increase in these properties.